IMPACTS OF CLIMATE CHANGE ON THE GLOBAL ECONOMY: AN IN-DEPTH ANALYSIS OF ECONOMIC LOSS PROJECTIONS AND MITIGATION STRATEGIES - Gunawan Widjaja; Tono Mahmudin; Loso Judijanto; Zainal Arifin; Iyad Abdallah Al- Shreifeen (CV. Adiba Aisha Amira, 2024)
Climate change is a defining challenge of our time, with far-reaching consequences for the global economy. This study provides a comprehensive examination of the economic impacts of climate change, focusing on projections of economic losses and the effectiveness of mitigation strategies. Our research combines quantitative analysis, case studies, and policy evaluation to offer a holistic perspective on this critical issue. Key findings of this research include the projection of substantial economic losses, potentially amounting to 2% of the global GDP by mid-century, if decisive measures are not taken. We analyze the vulnerabilities of critical sectors, such as agriculture and energy, and underscore the regional disparities in climate impacts through case studies. Adaptation and mitigation strategies are explored, emphasizing the economic benefits of proactive measures. This study is a vital resource for policymakers, businesses, and researchers, offering actionable insights to navigate the complex interplay between climate change and the global economy. It reiterates the urgency of addressing climate change's economic impacts and presents a roadmap for building resilience and seizing economic opportunities in a changing climate.